Revision Stapes Surgery: A Novel Technique of Overcoming Erosion of the Long Process of Incus Using Hydroxylapatite Cement and Shape Memory Piston. Issue 3 (March 2019) - Rouhani, Maral J.; Lavy, Jeremy
Abstract : Background: Stapes surgery is performed to treat hearing loss in patients with otosclerosis. Erosion of the long process of incus can occur postoperatively and requires demanding revision surgery to further improve the hearing. The authors describe a novel method of performing revision stapes surgery where there is erosion of the long process of incus. Methods: A retrospective case series analysis of a database of revision stapes operations performed by one surgeon between July 2013 and December 2017 at a tertiary center was carried out. 26 cases were identified where there was significant erosion of long process of incus. The ossicular chain in these cases was reconstructed using a novel technique of using cement to fix the piston prosthesis to the incus remnant. The full technique is described herein. The pre- and postoperative audiometric data were analyzed. Results: Mean preoperative air bone gap (ABG) was 29.3 dB and mean postoperative ABG was 9.9 dB. Of the 22 patients with recorded postoperative masked bone conduction thresholds, 16 had ABG closure to < 10 dB (72.7%). Conclusion: We have shown highly favorable outcomes using this novel technique in addressing erosion of the long process of incus in revision cases for patients with otosclerosis.